THE TECHNIQUE OF RESEARCH OF THE DEMPPING PROPERTIES OF THE ADAPTIVE AMORTIZOR WITH THE CONTROLLING THROTTLE - V. S. Konchak; S. V. Hitrikov; D. A. Shvets; Y. A. Bahdanau; V. L. Efremov (Informatika)
The research of the designed sample of the adaptive shock absorber, designed forthe use in the systems of cushioning of trucks operating in off-road conditions is considered. The test scheme and the equipment used for their testing are given. Methods for controlling the accuracy characteristics of the measuring and control equipment, modeling control processes for obtaining the characteristics of the test sample are considered. The methods and program of testing procedure are given.